Novel type of red-shifted chlorophyll a antenna complex from Chromera velia: II. Biochemistry and spectroscopy - Bína, David; Gardian, Zdenko; Herbstová, Miroslava; Kotabová, Eva; Koník, Peter; Litvín, Radek; Prášil, Ondřej; Tichý, Josef; Vácha, František (Biochimica et biophysica acta, 2014)
A novel chlorophyll a containing pigment-protein complex expressed by cells of Chromera velia adapted to growth under red/far-red illumination [1]. Purification of the complex was achieved by means of anion-exchange chromatography and gel-filtration. The antenna is shown to be an aggregate of ~20kDa proteins of the light-harvesting complex (LHC) family, unstable in the isolated form. The complex possesses an absorption maximum at 705nm at room temperature in addition to the main chlorophyll a maximum at 677nm producing the major emission band at 714nm at room temperature. The far-red absorption is shown to be the property of the isolated aggregate in the intact form and lost upon dissociation. The purified complex was further characterized by circular dichroism spectroscopy and fluorescence spectroscopy. This work thus identified the third different class of antenna complex in C. velia after the recently described FCP-like and LHCr-like antennas. Possible candidates for red antennas are identified in other taxonomic groups, such as eustigmatophytes and the relevance of the present results to other known examples of red-shifted antenna from other organisms is discussed. This work appears to be the first successful isolation of a chlorophyll a-based far-red antenna complex absorbing above 700nm unrelated to LHCI.
Keywords: F710 (diatoms); Chlorophyll fluorescence; Apicomplexa; chromatografie iontoměničová; fluorescenční spektrometrie; chlorofyl a; aniontoměniče; Light-harvesting complex; Chlorophyll; Chromera velia; Chlorophyll A; Chromatography, Gel; Circular Dichroism; chlorofyl; Spectrophotometry, Ultraviolet; Anion Exchange Resins; cirkulární dichroismus; gelová chromatografie; Red-shifted chlorophyll; Spectrometry, Fluorescence; Chromatography, Ion Exchange; spektrofotometrie ultrafialová